Obsessive–compulsive existential type: a dialectical-phenomenological approach - Fukuda, Lívia; Tamelini, Melissa; Messas, Guilherme (Frontiers in Psychology, 2023)
The clinical presentation of obsessive-compulsive patients is characterized by unwanted, intrusive, nonsensical, self-related, and recurrent ideas, thoughts, images, or impulses associated with active compulsive compensations. Under the operational diagnostic criteria adopted by the biological-and cognitive-oriented neopositivist medical paradigm, it is known as "obsessive-compulsive disorder." However, this paradigm has been criticized for its controversial assumptions, limited methodologies, theoretic biases, and inconsistency in producing practical outcomes. To bypass some of these issues, we propose a complementary approach that draws on and further develops existing psychopathological studies of the obsessive-compulsive anthropological condition based on dialectical phenomenological psychopathology. As such, we refer to the global clinical configuration as the "obsessive-compulsive existential type". Our theoretical inspiration comes from the classical phenomenological work on obsessions undertaken by Straus and Gebsattel, which identified the negative transformation of the obsessive-compulsive life-world or the endogenous emergence of the anti-eidos (diluting existential force). We then propose to broaden the concept of anti-eidos, especially in its dialectical correlation with eidos (unifying existential force), representing the existential dialectic between transformation and permanence. Next, we detail the dynamics of anthropological disproportions in obsessive-compulsive existential type, essentially the supremacy of the anti-eidos over the eidos. This primary imbalance modifies the obsessive-compulsive existential structure, consisting of polymorphic temporality; weakened intentionality; maladjusted calibration of distance with the world and others; an integral, isolated, besieged self with dwindling self-agency, and tense and over-protecting embodiment. We also analyze compensatory hyperreflexivity and compulsive rituals as expressions of structural counterbalancing designed to contain the primary structural disproportions and derangements. The heterogeneous obsessive-compulsive clinical manifestations are the complex result of the primary structural alteration and subsequent phenomenological compensations. They tend to be variable in temporal span and rarely assume a fixed form, hindering diagnosis. We correlate structural frameworks with multiple clinical examples. Finally, we raise some insights on how our study may contribute to scientific research and therapeutic proposals.